NEVANLINNA CHARACTERISTICS AND DEFECTIVE VALUES OF THE WEIERSTRASS ZETA FUNCTION - Korenkov, Mykola Ye.; Kharkevych, Yurii I.; Zajac, J.; Коренков, Микола Євгенович; Харкевич, Юрій Іліодорович; Зайонц, Я. (Ukrainian Mathematical Journal, 2011)
We determine the Nevanlinna characteristics of the Weierstrass zeta function and show that none of the values a ∈C is exceptional in Nevanlinna’s sense for this function.